2022
DOI: 10.3390/ijerph192013052
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Green and Historic Urban Environments and Mental Well-Being: Results from EEG and Psychometric Outcome Measures

Abstract: Previous studies have identified the benefits of exposure to green or historic environments using qualitative methods and psychometric measures, but studies using a combination of measures are lacking. This study builds on current literature by focusing specifically on green and historic urban environments and using both psychological and physiological measures to investigate the impact of virtual exposure on well-being. Results from the psychological measures showed that the presence of historic elements was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…The combination of psychometric measures and EEG analysis has revealed the lack of concordance in them with respect to experience from experimental videos. Existing research notes restoration of hedonic tone and stress reduction as a result of viewing historical elements in the architecture of the city without a significant effect on self-reported mental state of the presence of greenery, which, however, was accompanied by lower levels of alpha activity in the occipital regions of the brain as a reflection of visual attention [ 9 ]. Correspondingly, although VR technologies have been highly praised, their final effectiveness for cognitive training or emotional healing is not guaranteed and deserves fair-minded studies.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of psychometric measures and EEG analysis has revealed the lack of concordance in them with respect to experience from experimental videos. Existing research notes restoration of hedonic tone and stress reduction as a result of viewing historical elements in the architecture of the city without a significant effect on self-reported mental state of the presence of greenery, which, however, was accompanied by lower levels of alpha activity in the occipital regions of the brain as a reflection of visual attention [ 9 ]. Correspondingly, although VR technologies have been highly praised, their final effectiveness for cognitive training or emotional healing is not guaranteed and deserves fair-minded studies.…”
Section: Introductionmentioning
confidence: 99%
“…The participants identified social and physical environmental features in their neighbourhoods that elicited both positive and negative emotions, and relatedly, reflected on their mental health. The papers by Zhang et al [ 7 ] and Reece et al [ 8 ] focused on immediate responses to outdoor scenes with the presence of greenery and historical or heritage value. Zhang et al [ 7 ] found that the proportion of grass and water in a heritage landscape predicts emotional responses to historical landscapes and observed that deep-learning facial recognition was able to detect more subtle changes in valence than self-reported measures.…”
mentioning
confidence: 99%
“…Zhang et al [ 7 ] found that the proportion of grass and water in a heritage landscape predicts emotional responses to historical landscapes and observed that deep-learning facial recognition was able to detect more subtle changes in valence than self-reported measures. Reece et al [ 8 ] found that the presence of historical elements—but not greenery—was associated with self-reported emotional responses to outdoor urban settings, whereas brain activity responded more clearly to greenery. Focusing on transitional spaces between indoor and outdoor settings, which have received little research attention so far, Li et al [ 9 ] concluded that viewing curved elements in these spaces reduced both physiological and psychological stress more than viewing linear elements.…”
mentioning
confidence: 99%
See 2 more Smart Citations